Synthesis, structure and Hirshfeld surface analysis of the first coordination compound of 2-aminobenzoxazole - a case of the complex with cadmium - Razzokova, S.R.; Kadirova, Sh.A.; Sadullayeva, S.A.; Ibragimov, A.B. (Science and Education, 2023)
The article give information about synthesis, structure and Hirshfeld surface analysis of the first coordination compound of 2-aminobenzoxazole - a case of the complex with cadmium.